The relationship between high-sensitivity C-reactive protein and gallstones: a cross-sectional analysis - Zhimeng Jiang; Zhimeng Jiang; Huixin Jiang; Xingyu Zhu; Xingyu Zhu; Donglin Zhao; Donglin Zhao; Feifei Su (Frontiers in Medicine)
Background and objectiveHigh-sensitivity C-reactive protein (hs-CRP), a classical indicator of inflammation, holds significant clinical value in various diseases. The relationship between hs-CRP and gallstones, however, remains poorly studied at present. The relationship between hs-CRP and gallstones will be investigated in this study.MethodsData from the 2017–2020 National Health and Nutrition Examination Survey (NHANES) were analyzed, focusing on participants aged 20 years and older who provided complete hs-CRP and gallstone information. Due to the skewed distribution of hs-CRP, the data were log-transformed [Log (hs-CRP)] to achieve normalization. Logistic regression analysis, subgroup analysis, and smoothed fitted curves were applied to determine the relationship between Log (hs-CRP) and the presence of gallstones.ResultsThe study included 4,484 participants with an average Log (hs-CRP) of 1.18 ± 0.74. The prevalence of gallstones was 11.15%, increasing with higher Log (hs-CRP) levels (quartile 1: 8.31%; quartile 2: 8.76%; quartile 3: 11.98%; quartile 4: 16.36%; p < 0.0001). Adjusting for all covariates in Model 3, each 10-fold increase in hs-CRP [corresponding to a one-unit increase in log10 (hs-CRP)] corresponded to a 29% increased odds of gallstones prevalence [1.29 (1.12–1.49)]. The smoothed fitted curve showed a positive linear relationship between Log (hs-CRP) and gallstones prevalence. The results of subgroup analyses exhibited a more pronounced positive correlation in the 20–40 age group [1.70 (1.33, 2.16)], compared to those aged 40–60 years [1.22 (1.01, 1.48)], and 60–80 years [1.14 (0.98, 1.34)].ConclusionHigher Log (hs-CRP) levels are linked to a greater prevalence of gallstones. We still need to carry out further large prospective research to explore the causal relationship of this association.